Analysis of Consumer Protection Policy on the Use of Sharia Fintech Services in Indonesia - Nur Moh. Faiz Amin; Tajul Arifin (CV. Kalimasada Group, 2025)
This research is motivated by the many problems in the use of Fintec in economic transaction activities in contrast to what is in the policy on the use of sharia fintech services in Indonesia. The purpose of this study is to ensure that existing policies can provide maximum protection for consumers, especially in relation to the sharia principles underlying fintech operations. This study examines the applicable regulations, such as Fatwa DSN-MUI and OJK regulations, as well as the implementation practices of Islamic fintech in providing consumer protection. The results show that although consumer protection policies are adequate, challenges remain in terms of information transparency, dispute resolution, and effective supervision. This study suggests the need for clearer regulations and stricter supervision mechanisms to improve consumer protection in the Islamic fintech sector in Indonesia